Santa María Academy: Shaping the Heroes of Today with Tomorrow's Technology - Del Valle Mejías, María Elena (International Journal of Advanced Corporate Learning (iJAC), 2024)
Santa María Academy has successfully integrated advanced technology into its educational framework to enhance the learning experience of its students, preparing them for future careers in law enforcement and the military. The academy's innovative approach includes personalized coaching, interactive resources, and smart tools that cater to individual student needs. By leveraging artificial intelligence and real-time performance monitoring, Santa María Academy has significantly improved student outcomes, motivation, and engagement. This case study explores the key elements of their success, including the implementation of personalized learning plans, interactive podcasts, a smart syllabus, and a real-time performance dashboard. The academy's model serves as a benchmark for educational institutions aiming to merge traditional values with cutting-edge technology to produce well-rounded and highly skilled graduates.